The impact of obstructive sleep apnea on quality of life in children with asthma - Lisa Adhia Garina; Faisal Yunus; Ina Susianti Timan; Widhy Yudistira Nalapraya; Bambang Supriyatno (Paediatrica Indonesiana, 2022)
Background In children with asthma, obstructive sleep apnea (OSA) is a comorbidity of concern. The presence of OSA has been associated with asthma exacerbations and decreased quality of life. Leukotriene played a role in tonsil hypertrophy which is one of the risk factors for OSA. Objective To evaluate the influence of OSA on quality of life in children with asthma. Methods This cross-sectional study in asthmatic children aged 7?15 years was conducted from August 2020 to June 2021 at government elementary and primary high schools in Bandung, West Java, Indonesia. Asthma was diagnosed by peak expiratory flow rate (PEFR) and OSA was diagnosed by polysomnography. Leukotriene was examined by an ELISA method and quality of life assessed by the Pediatric Asthma Quality of Life Questionnaire (PAQLQ). Results Using the ISAAC questionnaire distributed through teachers to parents, 206 (6.9%) of 2,964 children stated that they had been diagnosed with asthma, 80 of whom were included in our study. Subjects’ mean age was 12 (SD 2) years and most were male. Intermittent asthma and history of allergy was dominant. Thirty-two children had OSA, mostly mild OSA. The mean level of leukotriene was not different between asthmatic children with and without OSA. The percentage of PEFR in asthmatic children with OSA was significantly lower than in those without OSA. The total PAQLQ score in asthmatic children with OSA and all PAQLQ domains were significantly lower than in those without OSA. Conclusion Obstructive sleep apnea in children with asthma is significantly associated with decreased peak expiratory flow rate and lower quality of life.